Upaya Peningkatan Pendapatan Rumah Tangga Melalui Pengembangan Usaha Pada Kelompok Petani Jamur Tiram Desa Pamotan Kabupaten Rembang - Siti Alliyah; Rikah Rikah (Journal of Dedicators Community, 2019)
The Community Service Program was carried out in Pamotan Village, Pamotan sub-district, Rembang Regency with partners from the Hanoman Makmur Group and Rizki Jamur. Pamotan Village is one of the villages in Rembang Regency where several of its residents have traditional oyster mushroom businesses and cultivation and need to get attention as well as assistance. The purpose of this program is to increase the income of the Hanoman Makmur Group and Rizki Jamur. The methodology used is counseling, entrepreneurship management training and practice in making baglogs, and business assistance. The results of this community service program include: 1) the formation of the Mushroom Pamot community which is a communication forum for mushroom farmers; 2) mushroom farmers are able to create mushroom baglog (media) independently; 3) has promotional media such as: brochures, product packaging, banners, blogs and business cards that are used as marketing media; 4) have an orderly and good record keeping.